Comunicação e hologramas de entretenimento: representações de artistas mortos em palcos de shows de música ao vivo - Kalil, Samara (2020)
This thesis is based on actual uses of holographic projections impulsed by the entertainment industries to investigate visual experiences and deceased artists representations in these events discussing how the perception of an absent sensitive frontier occurs by imagery and technology through Belting (2010, 2015), Debray (1993) and Baudrillard (1995, 1996a, 1996b). The work is structured in four chapters in which the first two reviews the former uses of the holographic technique grounded in historiccultural development and encompassing the anthropology of the images through comprehension the concepts of death, representation, and simulation (RICHARSON; WILTSHIRE, 2018; JOHNSTON, 2016; BURDEKIN, 2015; DOMINGUES, 2003, 2009; MANNONI, 2000; CRARY, 2012; VIRILIO, 2014; PARENTE, 2013; VILLAFAÑE, 2006; COUCHOT, 1993). The virtual, digital performance, metalepsis, and strangeness are studied concepts in the phenomenon using Schechner (2013), Dixon (2007), Taylor (2012), Pier (2016), Wolf (2016), Hofer (2011), Mori (2012), Jones, Benett & Cross (2015) references. The third chapter develops a methodologic strategy aiming at the communication field, mapping the past 30 years related to the researched object. The last chapter presents two points of observation and analysis: a) holographic performances recorded from videos of deceased artists occurred live; b) a live show in London 2019, from an observer's point of view. As a result, it indicates a schema of perceptive – understanding to this form of live image as an entertainment hologram – that occurs in “a circle” perspective experience, with metaleptic moves that should/can be considered/evaluated. Therefore, it proposes that the deceased artists already manage, through the holographic image modeling system, to partially subvert the logic of death if they maintain a safe distance from the fan/audience avoiding being a strange presence